The Comparative Study between Science and Social Students’ Scores on Learning Speaking Eleventh Year of SMA Negeri 13 Makassar - Mandan, Tree Wahyuni; Weda, Sukardi; Amin, Fatimah Hidayahni (International Journal of Language, Education, and Literature, 2025)
This research was aimed to measure (1) the comparison of the English speaking treated in Problem Based Learning between the students at eleventh year from social and science classes, to describe (2) the perceptions of the English teachers towards the implementation of teaching English speaking through Problem Based Learning. This method applied was mixed-method with comparative design in which 30 science and 30 social students in year eleventh of SMA Negeri 13 Makassar (XI. IPA 5 and XI. IPS 2) become the samples. The researcher used speaking skill test and interview as the research instruments. The speaking test was done in order to collect the data and it was conducted to identify the science and social scores in English speaking skill, especially in the three aspects of speaking skill: fluency, accuracy, and comprehension. The results showed that the science actually dominated the higher scores in all aspects of speaking, the mean score of science students reach 86.3407 while social students reach 76.9843. (1) The t-test was lower than P (0.000 < 0.05), which means that the (H0) of this research was rejected and (H1) was accepted. (2) English teachers perceptions regarding the effectiveness of Problem Based Learning model had positive perception Therefore, it can be inferred that the science students in year eleventh of SMA Negeri 13 Makassar have better scores in speaking skill than the social students through Problem Based Learning model.